Early identification of sleep bruxism among dental students: an observational study - Yunisa, Fahmi; Kurniasih, Indri; Putri, Vinanga Dentia; Biddinika, Muhammad Kunta (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Psychological conditions such as stress, anxiety, and depression can trigger sleep bruxism, a parafunctional activity. Dental students are one group that may experience psychological difficulties. Study workloads for dental students can cause stress and lead to sleep bruxism. This research aimed to identify the incidence of sleep bruxism among dental students. Participants were dental students of Universitas Muhammadiyah Yogyakarta (n = 200) aged 23–29 years, with 1–5 years of study periods. We adapted a questionnaire from the American Academy of Sleep Medicine to detect sleep bruxism. This questionnaire contains eight questions about the signs and symptoms experienced by respondents with sleep bruxism. The result of this study showed that only 18% of the participants had sleep bruxism. It can be concluded that the incidence of sleep bruxism in dental students is relatively low.